2019
DOI: 10.3390/cancers11101528
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TFF3 Enhances Sensitivity—and Overcomes Acquired Resistance—to Doxorubicin in Estrogen Receptor-Positive Mammary Carcinoma

Abstract: Dose-dependent toxicity and acquired resistance are two major challenges limiting the efficacious treatment of mammary carcinoma (MC) with doxorubicin. Herein, we investigated the function of Trefoil Factor 3 (TFF3) in the sensitivity and acquired resistance of estrogen receptor positive (ER+) MC cells to doxorubicin. Doxorubicin treatment of ER+MC cells increased TFF3 expression. The depletion of TFF3 by siRNA or inhibition with a small molecule TFF3 inhibitor (AMPC) synergistically enhanced the efficacy of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Following doxorubicin administration, an increase occurs in the expression of TFF3 and Akt that are responsible for cancer proliferation and inhibiting apoptosis. It has been reported that downregulation of TFF3 provides the way for enhancing apoptosis and doxorubicin sensitivity [ 81 ].…”
Section: Doxorubicin: Cancer Resistance and Side Effectsmentioning
confidence: 99%
“…Following doxorubicin administration, an increase occurs in the expression of TFF3 and Akt that are responsible for cancer proliferation and inhibiting apoptosis. It has been reported that downregulation of TFF3 provides the way for enhancing apoptosis and doxorubicin sensitivity [ 81 ].…”
Section: Doxorubicin: Cancer Resistance and Side Effectsmentioning
confidence: 99%
“…After its discovery, DOX was considered as the first option in treatment of cancer patients and showed promising clinical results. However, these ideal findings disappeared with development of DOX resistance [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin treatment of ER+MC cells increased TFF3 expression. The depletion of TFF3 enhanced the efficacy of doxorubicin in ER+breast cancer through the suppression of doxorubicin‐induced AKT activation and enhancement of doxorubicin‐induced apoptosis 37 . Additionally, overexpression of TFF3 decreased the sensitivity of cervical cancer cells to etoposide by increasing P‐glycoprotein (P‐gp) functional activity 38 .…”
Section: Discussionmentioning
confidence: 99%